OPINI GOING CONCERN DIPENGARUHI AUDIT TENURE, OPINI TAHUN SEBELUMNYA, AUDIT DELAY - Julianti, Ami; Mahpudin, Endang (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to determine how audit tenure, previous year's audit opinion, and audit delays affect going concern audit opinions, especially in textile and garment sub-sector companies for 5 years. This study has a descriptive quantitative research type. The target population is textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. A total of 22 companies collected population data. There are a sample of 11 companies selected through the purposive sampling method. Data were collected through secondary sources, especially the textile and garment sub-sector. The limitation in the study is only in one sector so it is recommended for further researchers to add other sectors. The analysis method used is logistic regression with the help of SPSS 25 software. The findings state that partially going concern audit opinions are not affected by audit tenure. Conversely, previous year's audit opinions and audit delays have an effect on going concern audit opinions. Simultaneously, the findings show that the dependent variable is affected by the audit engagement period, previous year's opinion, and audit delays.